The Impact of Divorce on Children’s Social Behavior - Roza, Selvina Elia; Irman, Irman; Silva, Ferro (Yayasan Minang Darussalam, 2024)
Divorce is the breaking of the marriage bond between husband and wife by court decision and there are sufficient reasons, that between husband and wife can no longer live in harmony. Common cases of divorce, social, economic and age factors when married. The purpose of this study is to know, examine and explain the impact of parental divorce on children's social behavior. The results of this study show that the impact of divorce on children's social behavior has a major influence in the negative direction. This study uses the literature review method by reviewing several existing articles, the results of the study show that divorce that occurs is very influential on children's social behavior, so that children of divorce victims need to get psychological guidance, or guidance from BK teachers.